The postcolonial subject in transit: migration, borders and subjectivity in contemporary African diaspora literature - Fongang, Delphine (Transforming Literary Studies, 2018)
The Postcolonial Subject in Transit presents in-depth analyses of the complex transitional migratory identities evident in emerging African diasporic writings. It provides insights into the hybridity of the migrant experience, where the migrant struggles to negotiate new cultural spaces. It shows that while some migrants successfully adapt and integrate into new Western locales, others exist at the margins unable to fully negotiate cultural difference. The diaspora becomes a space for opportunities and economic mobility, as well as alienation and uncertainties. This illuminates the heterogeneity of the African diasporic narrative, expanding the dialogue of the diaspora, from one of simply loss and melancholia to self-realization and empowerment.